Perlindungan Hukum Terhadap Pelapor Kasus Peredaran Gelap Narkotika Dalam Perspektif Hukum Islam - Ramadhan Harlis, Habib; Zulkarnain (IAIN Langsa, 2024)
The illicit drug trade has become a serious threat in various regions, including Medan Perjuangan District, Medan City. Legal protection for whistleblowers reporting cases of illicit drug trafficking is crucial in curbing this trade. This research aims to identify the legal protections available to whistleblowers of illicit drug trafficking cases from the perspective of both positive law and Islamic law. The focus is to understand whether the existing legal systems provide adequate protection for whistleblowers. This article falls under library research with a qualitative approach. The methodology used is a normative legal study by analyzing data related to the applicable legal regulations in Indonesia, particularly concerning the protection of whistleblowers in cases of illicit drug trafficking. The results of the study indicate that although there is a legal framework governing the protection of whistleblowers, its implementation still faces several challenges on the ground. However, certain measures have been taken to improve the effectiveness of legal protection for whistleblowers in cases of illicit drug trafficking.